Use of Teduglutide in Children With Intestinal Failure: A Systematic Review - Gigola, Francesca; Cianci, Maria Chiara; Cirocchi, Roberto; Ranucci, Maria Chiara; Del Riccio, Marco; Coletta, Riccardo; Morabito, Antonino (Frontiers in Nutrition, 2022)
Background and Objectives Short-bowel syndrome (SBS) results from the loss of a significant portion of the small intestine leading to a state of malabsorption. After an intestinal loss, there is a process of adaptation involving the Glucagon-Like Peptide-2 (GLP-2), an enteroendocrine peptide also involved in nutrient absorption. Teduglutide is a recombinant analog of GLP-2 approved in 2016 to treat selected SBS pediatric patients who are dependent on parenteral support. The present systematic review aims to evaluate the efficacy of Teduglutide in pediatric patients with SBS in reducing the need for parenteral nutrition (PN). Materials and Methods We performed a literature search on MEDLINE and Embase to include articles up to November 2021. We included articles that involved using Teduglutide in the SBS pediatric population to define its efficacy in reducing the need for PN. The key words used were GLP-2, teduglutide, child. Results Fourteen studies completely fulfilled the inclusion criteria. Two hundred 23 patients were treated with Teduglutide, and the median duration of treatment was 45 weeks (IQR: 36–52.5 weeks). One-hundred and fifty-two patients were treated with 0.05 mg/Kg/d of subcutaneous Teduglutide, 38 received 0.025 mg/Kg/d and 8 received either 0.125 mg/Kg/d or 0.20 mg/Kg/d. A total of 36 patients achieved enteral autonomy (EA) after a median of 24 weeks of treatment (IQR: 24–48 weeks) and 149 patients showed a reduction in PN needs in terms of volume, calories, or hours per day. Eleven studies reported complications: gastrointestinal were the most common, with 89 cases reported in treated patients and 11 in non-treated patients. Conclusion Teduglutide appears safe and effective in reducing PN requirements and improving EA in the pediatric population. However, more studies are needed to understand its efficacy in the long term and after discontinuation and possible complications. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022301593].